In Vitro Culture of the Insect Endosymbiont Spiroplasma poulsonii Highlights Bacterial Genes Involved in Host-Symbiont Interaction - Masson, Florent (mBio, 2018)
Endosymbiotic bacteria associated with eukaryotic hosts are omnipresent in nature, particularly in insects. Studying the bacterial side of host-symbiont interactions is, however, often limited by the unculturability and genetic intractability of the symbionts. Spiroplasma poulsonii is a maternally transmitted bacterial endosymbiont that is naturally associated with several Drosophila species. S. poulsonii strongly affects its host’s physiology, for example by causing male killing or by protecting it against various parasites. Despite intense work on this model since the 1950s, attempts to cultivate endosymbiotic Spiroplasma in vitro have failed so far. Here, we developed a method to sustain the in vitro culture of S. poulsonii by optimizing a commercially accessible medium. We also provide a complete genome assembly, including the first sequence of a natural plasmid of an endosymbiotic Spiroplasma species. Last, by comparing the transcriptome of the in vitro culture to the transcriptome of bacteria extracted from the host, we identified genes putatively involved in host-symbiont interactions. This work provides new opportunities to study the physiology of endosymbiotic Spiroplasma and paves the way to dissect insect-endosymbiont interactions with two genetically tractable partners.